Positron emission tomography-magnetic resonance liver parenchyma attenuation correction artifact in secondary hemochromatosis - Robert Matthews; Michael Joseph Salerno; Paul Vaska; Halley Hindman (World Journal of Nuclear Medicine)
Positron emission tomography-magnetic resonance (PET-MR) hybrid imaging is a relatively new imaging modality combining the superb MR contrast capabilities among different soft-tissue structures with the high sensitivity of PET functional imaging. With the development of any new technology, a variety of limitations will be encountered including the introduction of new types of artifacts. In this case report, we present a restaging PET-MR scan for multiple myeloma that showed severely decreased fluorodeoxyglucose activity in the liver on the PET attenuated corrected images. Careful analysis showed the cause of the decreased activity to be the improper density assignment on the mu map caused by iron deposition within the liver. Follow-up imaging showed reversal of the phenomena following improvement of liver disease.